PARITAS DENGAN KEPATUHAN ANTENATAL CARE - wijayanti, adhika (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2024)
Compliance with implementation antenatal care for pregnant women, this can be done by looking at the coverage figures for pregnant women's visits to KI and K4. Pregnant women who carry out routine activities antenatal care useful for detecting pregnancy complications. The aim of this research was to determine the relationship between parity and compliance antenatal care pregnant mother. The research design used is an analytical survey method with an approach Cross Sectional. The population of this study were all pregnant women at the Danurejan I Community Health Center, Yogyakarta City, at the time the research was conducted, totaling 47 respondents taken using a simple random sampling technique. The results of this study show that there is a relationship between parity and compliance antenatal care pregnant women at the Danurejan I Community Health Center, Yogyakarta City (ρ value=0.000).